WARM TO COLD WATER CARBONATE FORMATION DURING THE ORDOVICIAN AND THE JURASSIC: EXAMPLES FROM IRAN, AUSTRALIA, AND ENGLAND (Journal of Sciences, Islamic Republic of Iran)
Isotope data from bulk carbonates, micrite, marine calcite cements, non-skeletal grains and brachiopods indicate deposition of a wide spectrum of warm to cold water carbonates during the Ordovician and the Jurassic. This isotopic interpretation is supported by warm to cold climatic models proposed for the Ordovician and the Jurassic. These carbonates formed during the Greenhouse mode (conditions similar to present day) and Icehouse mode. Isotopic equilibrium trends of carbonate minerals indicate an originally aragonite-calcite mixture during the late Ordovician of Tasmania and Late Jurassic of Iran (Kopet-Dagh Basin-Sarakhs area) corresponding to warm temperatures; whereas originally calcitic mineralogy deposited during the Mid Jurassic in England and Scotland, and the Late Jurassic at Mallorca Island, Spain, correspond to cool to cold water temperatures. Sedimentological features of these ancient limestones are similar to modern warm to cold water carbonates.